Plant pathology in India : One hundred years of plant pathology in India - Chahal, S. S. (Sarbjit S.); Khetarpal, R. K.; Thind, T. S.; Indian Society of Mycology and Plant Pathology (Jodhpur : Scientific Publishers (India) on behalf of Indian Society of Mycology and Plant Pathology, 2006)
Contributed articles.
Includes bibliographical references and Index.
Keywords: Plant diseases -- India